That so-called papanicolaou: women’s social representations about the screening test for cervical cancer - Silva, Sílvio Éder Dias da; Vasconcelos, Esleane Vilela; Santana, Mary Elizabeth de; Rodrigues, Ivaneide Leal Ataide; Mar, Dayse Farias; Carvalho, Francilene da Luz (Revista da Escola de Enfermagem da USP, 2010)
This research aims to identify women's social representations of women regarding cervical cancer and describe the relationship of these social representations with preventive care. The study used a qualitative-exploratory approach, with the theory of social representations as the theoretical-conceptual support. Data collection was performed using two techniques: the free association of words and the semi-directed interview with open questions. The thematic analysis technique was used for data interpretation. The research resulted in two thematic units: cervical cancer: an early treatable wound and the screening test: taking because of fearing. It was observed that women have great fear of having cervical cancer and, therefore, recognize the importance of the screening test and see it as an act of self-care towards their health.